Agrobacterium‐mediated transformation via establishment of stable tissue culture system in Zoysia matrella (L.) Merrill 'Wakaba'. (20th December 2022) - Ng, Hwan May; Gondo, Takahiro; Ushiyama, Mari; Cho, Shin; Maemura, Soko; Hashiguchi, Masatsugu; Tanaka, Hidenori; Akashi, Ryo
Abstract: Zoysia matrella (L.) Merrill is a perennial C4 warm‐season turfgrass grown for landscapes, golf courses, sports fields and recreation parks. To create a new breeding method by genome editing, an efficient genetic transformation system is essential. In this study, we report the efficient protocol of Agrobacterium ‐mediated transformation through the establishment of a stable tissue culture system for Z. matrella 'Wakaba'. The embryogenic callus was induced from shoot apices of nodal segments incubated in Murashige and Skoog (MS) medium containing 2 mg/l 2, 4‐dichlorophnoxyacetic acid (2, 4‐D), 0.1 mg/l 6‐benzylaminopurine (BAP) and 5 μM CuSO4 (MS‐DBC). Repeated subculture of compact high‐quality callus in MS‐DBC medium produced a highly regenerative callus with dense pre‐embryogenic clusters, and it was used as a transformation target. Agrobacterium strain EHA105 harboring pANIC8B vector containing the β‐glucuronidase gene ( GUS ) and hygromycin B phosphotransferase gene was used. Agrobacterium ‐infected calli were cocultured for 5 days with 100 μM acetosyringone and then subjected to selection pressure of 50 mg/l hygromycin. This optimized protocol yielded transformation efficiencies of up to 6.6%. Southern blot analysis verified one to three copies of the GUS gene in different independent transgenic plants. All transgenic plants were morphologically normal, and the GUS expressions were stable. Our optimized in vitro and transgenic system will facilitate the new breeding technology of genome editing in zoysiagrass.